International migration and the rise of urban militant networks in the Mediterranean - Lacroix, Thomas; Furri, Filippo; Hombert, Louise (Frontiers in Political Science, 2022)
From the US to Italy, from Brazil to Japan, cities from all over the world are increasingly vocal on migration issues. Advocating for alternative approach to immigrants' welcome, their stand and policies may at times be in blunt contradiction with national approaches. This paper gives an overview of this new form of urban militancy, its recent evolution, its forms, its networks. Drawing on case studies in France, Spain and Italy, it seeks to explain why the Mediterranean has been an important setting for the politicization of municipal involvement and the rise of multi-actor power assemblage of municipalities and voluntary organizations.